Excitation Energy Dependent Ultrafast Luminescence Behavior of CdS Nanostructures - Karras, Christian; Roeder, Robert; Paa, Wolfgang; Ronning, Carsten; Stafast, Herbert (ACS Photonics, 2017)
Selected semiconductor nanostructures provide extremely localized coherent light sources. Here an ensemble of CdS nanostructures was excited by UV/vis femtosecond laser pulses and their ultrafast luminescence characteristics were investigated as functions of the pulse energy fluence and the photon quantum energy. All optical Kerr gating enabled studies of the emission dynamics with a time resolution of 150 fs avoiding any influence on the CdS emission. The initially observed emission built up after a delay of 0.1-3 ps and decayed rapidly in a biexponential way, strongly dependent on both the laser energy fluence and the quantum energy. The central wavelength of the emission spectrum revealed a significant blue-shift within the first few ps followed by a transient red-shift relative to spontaneous excitonic emission of CdS. All findings are mainly attributed to stimulated radiative carrier recombination in the laser excited electron-hole plasma after its thermalization with the CdS lattice.
CRIS-Team Scopus Importer:2023-04-20
Keywords: CdS; hot charge carriers; lasing; nanostructures; stimulated emission; ultrafast relaxation